2021
DOI: 10.1177/09544062211016889
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cycloidal reducer output mechanism while taking into account machining deviations

Abstract: There are three main rolling nodes in the cycloidal gear reducer: the gear, output mechanism and central bearing. To transfer the drive from the active side to the output side of the gear, an output mechanism is used, which is formed by bushings mounted on pins located in the output shaft. During the operation of the reducer, the bushings roll around the wheel holes with a cycloidal contour. Using the structure and geometry of the output mechanism, an analysis of the backlash distribution in it was conducted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…According to Bednarczyk's article titled "Analysis of the Cycloidal Reducer Output Mechanism Considering Machining Variations," the findings indicate that the distribution of backlash, forces, and contact pressures is heavily influenced by the tolerances of the bushings' arrangement and the holes in the planet wheel. The research in this field has contributed to the development of knowledge in the area of selecting various machining variations with regard to the resulting cutting forces [16].…”
Section: Overview Of the Papers Published In The Field Of The Issue A...mentioning
confidence: 99%
“…According to Bednarczyk's article titled "Analysis of the Cycloidal Reducer Output Mechanism Considering Machining Variations," the findings indicate that the distribution of backlash, forces, and contact pressures is heavily influenced by the tolerances of the bushings' arrangement and the holes in the planet wheel. The research in this field has contributed to the development of knowledge in the area of selecting various machining variations with regard to the resulting cutting forces [16].…”
Section: Overview Of the Papers Published In The Field Of The Issue A...mentioning
confidence: 99%
“…It is not only in the meshing that mechanical power losses occur that due to machining tolerances but also in the output mechanism. In [13], a model for the backlash and force distribution in the output mechanism of a cycloidal reducer, consisting of pins and bushings, was developed and analyzed with regard to machining deviations.…”
Section: Introductionmentioning
confidence: 99%
“…Matejić et al [25] provided efficiency analysis for a new two-stage cycloid drive concept based on losses generated by friction, and drew comparisons with the current schemes in practice. Bednarczyk et al [26] found that the forces, contact pressures and backlash distribution were strongly determined by the tolerance of the radius of the bushings' arrangement and holes in the planet wheel by analyzing the cycloidal reducer output mechanism, considering machining deviations. Blagojević et al [27] designed a new concept on a two-stage cycloidal speed reducer, in which only one cycloid disc was used per stage to enhance the structure compactness, and conducted a simulation to confirm its dynamic balance and stability.…”
Section: Introductionmentioning
confidence: 99%